Human Capital Investment and Globalization in Extortionary States - Fredrik Andersson; Kai A. Konrad (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper considers education investment and public education policy in closed and open economies with an extortionary government. The extortionary government in a closed economy chooses an education policy in order to overcome a hold-up problem of time-consistent taxation similar to benevolent governments. The two types of government differ in their education policies if highly productive labor is mobile. Extortionary governments incentives for a policy that stimulates higher private education efforts vanish; instead they have incentives to prevent individuals from mobility-increasing education investment. Tax competition therefore reduces hold-up problems of time-consistent extortionary taxation, but introduces other distortions that reduce workers' utility.
Keywords: 330; migration; education; globalization; commitment; time consistent income taxation; globalisation